New Aspects of Library Design - Hohmann, Tina (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
New planning principles are required to meet the changing needs of the users of the library of the future. The digital revolution has changed the appearance of today’s libraries entirely. The majority of today’s information resources are of a non-physical nature and accessing information is more varied and complex. The traditional role as asset keeper is one of many tasks today. The recently completed examples of Dresden and Göttingen State- and University Library, the Seattle Public Library and the Idea Stores in London, all of them highly popular and frequented, show current trends in library design. What do they offer their visitors? • access to information • guidance (information skills) • possibility for communication • working environment • inspiring atmosphere Their design is based on the following main principles: • Access to the library and its medias should be obvious and easy for everybody. • There should be multifarious space for formal and informal communication between customers and staff. • The interior should offer an attractive and comfortable environment for both customers and staff. • The library building should adequately represent its institutional philosophy and aims. • Its building design, structure and appliances should give consideration to sustainability.